2017
DOI: 10.1021/acs.orglett.7b01876
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomeric Chiral Diiododienes (Z,Z)-2,3-Di(1-iodoalkylidene)tetralins: Synthesis, Enantiomeric Resolution, and Application in Asymmetric Catalysis

Abstract: The C-symmetric tetralin-fused 1,4-diiodo-1,3-butadiene derivatives, (Z,Z)-2,3-di(1-iodoalkylidene)tetralin 1a-c, are atropisomeric and can be resolved into the two persistent axially chiral enantiomers by HPLC on a chiral stationary phase. The enantiomerically pure compounds can serve as chiral organocatalysts for dearomatizing spirolactonization to show good performance in up to 73% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…For instance, Ogasawara et al synthesized conformationally rigid C2-symmetric atropisomeric chiral diiododiene 314 and successfully applied as chiral organocatalyst in the dearomatizing spirolactonization of 1-naphthols 309 to yield (S)-spirolactone 310 with ee up to 73% (Scheme 85). 117 Further, Imrich and Ziegler prepared the first carbohydrate-based chiral aryl iodide catalyst 315 by condensing partially protected glucosides with iodoresorcinol via Mitsunobu reaction. 118 This catalyst was further employed for the oxidative spriolactonisation of 309 to provide spirolactone 312 in 77% yield with er up to 80:20.…”
Section: Synthesis Of Spirocyclic Heterocyclesmentioning
confidence: 99%
“…For instance, Ogasawara et al synthesized conformationally rigid C2-symmetric atropisomeric chiral diiododiene 314 and successfully applied as chiral organocatalyst in the dearomatizing spirolactonization of 1-naphthols 309 to yield (S)-spirolactone 310 with ee up to 73% (Scheme 85). 117 Further, Imrich and Ziegler prepared the first carbohydrate-based chiral aryl iodide catalyst 315 by condensing partially protected glucosides with iodoresorcinol via Mitsunobu reaction. 118 This catalyst was further employed for the oxidative spriolactonisation of 309 to provide spirolactone 312 in 77% yield with er up to 80:20.…”
Section: Synthesis Of Spirocyclic Heterocyclesmentioning
confidence: 99%
“…Furthermore, the C 2 ‐symmetric tetralin‐fused conformationally rigid atropisomeric chiral diiodides, ( M )‐ 30 a – c , were synthesized and utilized as precatalysts for the enantioselective dearomatization of 7 a in the presence of m CPBA by Ogasawara and Dohi (Figure 5). All the chiral diiodides ( M )‐ 30 a – c catalyze the dearomatization reaction efficiently, although ( M )‐ 30 c exhibited the best enantioselectivity (73% ee ) [39] …”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Hence, chiral iodoarene 2g was chosen as the optimal catalyst for this oxidative reaction. Next, evaluation of different solvents in the presence of catalyst 2g revealed that dichloromethane was the best solvent with the highest yield and enantioselectivity (entry 7 versus entries [11][12][13][14][15][16][17].…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…8 In 2008, Kita and co-workers reported excellent work on the asymmetric dearomative spirolactonization of 1-naphthol derivatives catalyzed by the structurally rigid C 2 -symmetric 1,1′-bisindane-based iodoarene. 9 Recently, Ishihara, 10 Ibrahim, 11 and Dohi 12 developed a series of C 2 -symmetric iodoarenes (Figure 1) for the same transformation. Although there have been a few reports on asymmetric spirolactonization catalyzed by C 1 -symmetric iodoarene, 13 to the best of our knowledge, hitherto, there has been no report on the use of C 1 -symmetric iodoarene in this important reaction.…”
mentioning
confidence: 99%